2021
DOI: 10.1186/s40104-021-00612-z
|View full text |Cite
|
Sign up to set email alerts
|

Galacto-oligosaccharides improve barrier function and relieve colonic inflammation via modulating mucosa-associated microbiota composition in lipopolysaccharides-challenged piglets

Abstract: Background Galacto-oligosaccharides (GOS) have been shown to modulate the intestinal microbiota of suckling piglets to exert beneficial effects on intestinal function. However, the modulation of intestinal microbiota and intestinal function by GOS in intestinal inflammation injury models has rarely been reported. In this study, we investigated the effects of GOS on the colonic mucosal microbiota composition, barrier function and inflammatory response of lipopolysaccharides (LPS)-challenged suck… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 60 publications
(61 reference statements)
1
20
0
2
Order By: Relevance
“…At the genus level, DSS can reduce the relative abundance of potentially beneficial bacteria and the consumption of Rg1 can partly counteract the effect of DSS. Studies have reported that norank_f _ Muribaculaceae may be a bacterium enriched in the healthy intestinal environment and may be potentially beneficial for relieving inflammation ( 33 , 39 , 40 ). In our study, DSS can significantly reduce the relative abundance of norank_f_Muribaculaceae , while the relative abundance of norank_f_Muribaculaceae was increased after Rg1 treatment compared with the DSS group.…”
Section: Discussionmentioning
confidence: 99%
“…At the genus level, DSS can reduce the relative abundance of potentially beneficial bacteria and the consumption of Rg1 can partly counteract the effect of DSS. Studies have reported that norank_f _ Muribaculaceae may be a bacterium enriched in the healthy intestinal environment and may be potentially beneficial for relieving inflammation ( 33 , 39 , 40 ). In our study, DSS can significantly reduce the relative abundance of norank_f_Muribaculaceae , while the relative abundance of norank_f_Muribaculaceae was increased after Rg1 treatment compared with the DSS group.…”
Section: Discussionmentioning
confidence: 99%
“…Both the Muribaculaceae family and the Alloprevotella genus significantly increased in the WT mice with alcohol drinking, which corroborates previous findings in alcoholic patients [ 47 ]. Lastly, the Alloprevotella genus has been associated with intestinal permeability and inflammation [ 48 , 49 ], which are common effects of alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Before GOS was dissolved in physiological saline, the physiological saline was placed in a hot water bath until the temperature of physiological saline was approximately 37 °C. During 13 d after birth, all piglets in the LPS + GOS group were orally administered GOS solution (1 g GOS/kg body weight [ 8 , 23 ]) per day. Meanwhile, all piglets in the CON group and the LPS group were orally administered the same volume of physiological saline.…”
Section: Methodsmentioning
confidence: 99%